2020
DOI: 10.21203/rs.3.rs-132211/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Scopolamine-Induced Delirium Promotes Neuroinflammation and Neuropsychiatric Disorder in Mice

Abstract: Postoperative delirium is a common neuropsychiatric syndrome resulting a high postsurgical mortality rate and decline in postdischarge function. Extensive research has been performed on both human and animal delirium models due to their clinical significance, focusing on systematic inflammation and consequent neuroinflammation playing a key role in the pathogenesis of postoperative cognitive dysfunctions. Since animal models are widely utilized for pathophysiological study of neuropsychiatric disorders, this s… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 55 publications
0
3
0
Order By: Relevance
“…The observed hyperactivity and increased exploration suggested that rats were less anxious in the maze. This is supported by Walsh and Cummins [43], Jafarian et al [22] and Cheon et al [10] who demonstrated that a high frequency of the number of peripheral square crossing and rearing in open field test indicating increased locomotor activity and/or a lower level of anxiety. In addition, Walsh and Cummins [43] and Stanford [39] reported that rats spent most of their time in the central area and explore more in open field test reflect a low level of anxiety.…”
Section: Discussionmentioning
confidence: 64%
See 2 more Smart Citations
“…The observed hyperactivity and increased exploration suggested that rats were less anxious in the maze. This is supported by Walsh and Cummins [43], Jafarian et al [22] and Cheon et al [10] who demonstrated that a high frequency of the number of peripheral square crossing and rearing in open field test indicating increased locomotor activity and/or a lower level of anxiety. In addition, Walsh and Cummins [43] and Stanford [39] reported that rats spent most of their time in the central area and explore more in open field test reflect a low level of anxiety.…”
Section: Discussionmentioning
confidence: 64%
“…Control group; injected with saline intraperitoneally (i.p); and Scopolamine hydrobromide-treated group (SCO) administered SCO at a dose of 2 mg/kg, i.p. dissolved in saline solution [5,10] daily for seven weeks.…”
Section: Animalsmentioning
confidence: 99%
See 1 more Smart Citation